Will the last be the first? Ranking German macroeconomic forecasters based on different criteria - Tim Köhler; Jörg Döpke (Empirical Economics, 2022)
We rank the quality of German macroeconomic forecasts using various methods for 17 regular annual German economic forecasts from 14 different institutions for the period from 1993 to 2019. Using data for just one year, rankings based on different methods correlate only weakly with each other. Correlations of rankings calculated for two consecutive years and a given method are often relatively low and statistically insignificant. For the total sample, rank correlations between institutions are generally relatively high among different criteria. We report substantial long-run differences in forecasting quality, which are mostly due to distinct average forecast horizons. In the long-run, choosing the criterion to rank the forecasters is of minor importance. Rankings based on recession years and normal periods are similar. The same does hold for rankings based on real-time vs revised data.
Keywords: 330; Macroeconomic forecasts; Ranking; Germany